Multidisciplinary Approach to the Treatment of Obese Adolescents: Effects on Cardiovascular Risk Factors, Inflammatory Profile, and Neuroendocrine Regulation of Energy Balance - Ana Raimunda Dâmaso; Aline de Piano; Raquel Munhoz da Silveira Campos; Flávia Campos Corgosinho; Wolfgang Siegfried; Danielle Arisa Caranti; Deborah Cristina Landi Masquio; June Carnier; Priscila de Lima Sanches; Patrícia Leão da Silva; Cláudia Maria Oller Nascimento; Lila Missae Oyama; et al. (International Journal of Endocrinology)
The prevention of obesity and health concerns related to body fat is a major challenge worldwide. The aim of this study was to investigate the role of a medically supervised, multidisciplinary approach, on reduction in the prevalence of obesity related comorbidities, inflammatory profile, and neuroendocrine regulation of energy balance in a sample of obese adolescents. A total of 97 postpuberty obese adolescents were enrolled in this study. Body composition, neuropeptides, and adipokines were analysed. The metabolic syndrome was defined by the International Diabetes Federation (IDF). The abdominal ultrasonography was performed to measure visceral, subcutaneous fat and hepatic steatosis. All measures were performed at baseline and after one year of therapy. The multidisciplinary management promoted the control of obesity reducing body fat mass. The prevalence of metabolic syndrome, asthma, nonalcoholic fatty liver disease (NAFLD), binge eating, and hyperleptinemia was reduced. An improvement in the inflammatory profile was demonstrated by an increase in anti-inflammatory adiponectin and reduction in proinflammatory adipokines, plasminogen activator inhibitor-1, interleukin-6 concentrations, and in the Lep/Adipo ratio. Moreover, a reduction in the AgRP and an increase in the alfa-MSH were noted. The multidisciplinary approach not only reduced obesity but also is efficacious in cardiovascular risk factors, inflammatory profile, and neuroendocrine regulation of energy balance.